Vaccination and you - Cohen, Daniel; Petie, Haris (New York : J. Messner, 1969)
Discusses the causes of disease, how vaccinations work, and the history of vaccines for such diseases as smallpox, diphtheria, polio, and measles.
includes bibliographical references and index.
Keywords: Vaccination -- Juvenile literature; Vaccination